2005
DOI: 10.1021/es0481070
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Sources of Unsaturated Zone and Groundwater Nitrate Contamination Using Nitrogen and Oxygen Stable Isotopes at the Hanford Site, Washington

Abstract: The nitrogen and oxygen isotopic compositions of nitrate in pore water extracts from unsaturated zone (UZ) core samples and groundwater samples indicate at least four potential sources of nitrate in groundwaters at the U.S. DOE Hanford Site in south-central Washington. Natural sources of nitrate identified include microbially produced nitrate from the soil column (delta15N of 4 - 8 per thousand, delta18O of -9 to 2 per thousand) and nitrate in buried caliche layers (delta15N of 0-8 per thousand, delta 18O of -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…In deep groundwater, Murgulet and Tick (2013) found that δ 18 O-NO 3 − and δ 15 N-NO 3 − values in the coastal aquifer of the Alabama, USA, indicated that the mixing ratios of sewage and fertilizer were consistent with the study area's land use. Singleton et al (2005) found that industrial sources contributed to the major nitrate plumes in groundwater below that those observed in the northeastern USA, where the former's area is 100 times smaller than the latter's. The data highlighted above show that seasonal and spatial changes are the primary factors influencing δ 15 N-NO 3 − and δ 18 O-NO 3 − values.…”
Section: Introductionmentioning
confidence: 86%
“…In deep groundwater, Murgulet and Tick (2013) found that δ 18 O-NO 3 − and δ 15 N-NO 3 − values in the coastal aquifer of the Alabama, USA, indicated that the mixing ratios of sewage and fertilizer were consistent with the study area's land use. Singleton et al (2005) found that industrial sources contributed to the major nitrate plumes in groundwater below that those observed in the northeastern USA, where the former's area is 100 times smaller than the latter's. The data highlighted above show that seasonal and spatial changes are the primary factors influencing δ 15 N-NO 3 − and δ 18 O-NO 3 − values.…”
Section: Introductionmentioning
confidence: 86%
“…Samples were analyzed following a version of the denitrifier method (Sigman et al 2001;Singleton et al 2005). Isotopic analysis was conducted at Lawrence Livermore National Laboratory on an IsoPrime continuous-flow mass spectrometer.…”
Section: Nutrient Concentration and Nitrate Isotope Ratiosmentioning
confidence: 99%
“…Both low-level waste and natural nitrate flushed from the vadose zone appear to be significant sources of groundwater contamination (Singleton et al 2005). Groundwater samples generally fell in a range between synthetic nitrate and natural nitrate found in uncontaminated vadose zone core.…”
Section: Chlorine-36mentioning
confidence: 99%